Coupled Engine–Fuel System Optimization for Energy Performance and Emission Control under High-Altitude Operating Conditions - Rocha-Hoyos, Juan Carlos; Cevallos Carvajal, Alex Santiago; Noroña Merchán, Marco Vinicio; Leguisamo Milla, Julio César; Pancha-Ramos, Johnny; Piure Cuenca, Hugo Andrés; Garcia-González, Anthony Segundo (International Journal of Aquatic Research and Environmental Studies, 2026)
Improving fuel efficiency and reducing emissions in spark-ignition engines, especially under high-altitude conditions, requires a comprehensive understanding of the complex interplay between engine architecture and fuel properties. This study critically examines the exhaust emissions and fuel performance of BT and SC vehicles using two gasoline types, EX and EC, selected via a statistically robust sampling method based on the characterization of Ecuador’s spark-ignition vehicle fleet. Experimental evaluations were conducted at 2,500 meters above sea level, utilizing dynamometer tests with the IM 240 driving cycle integrated into the vehicle inspection and maintenance system to quantify emissions of carbon monoxide, hydrocarbons, and nitrogen oxides. A factorial experimental design and Response Surface Methodology were employed to assess the effects of engine displacement, compression ratio, and fuel composition, modeling both nonlinearities and interactions through second-order polynomials. Results reveal that vehicle specific factors, particularly displacement and compression ratio, are the predominant determinants of fuel consumption and emission profiles. Both the use of oxygenated biofuels such as EC gasoline significantly reduced incomplete combustion byproducts CO and HC, though NOx emissions exhibited a complex response, highlighting a non-linear relationship dependent on both fuel and operational context. In addition, statistical analysis demonstrated significant differences primarily attributable to vehicle type, with fuel type and their interaction also contributing. It was important to emphasize These findings underscore that optimizing both combustion settings and fuel formulation is essential to achieving substantial gains in efficiency and emissions control, particularly in the challenging context of high-altitude operation. Finally, the study provides analytical evidence that targeted strategies—incorporating advanced engine calibration and tailored fuel blends—are critical for meeting stringent environmental standards without compromising energy performance and offers a framework for future research and policy in sustainable mobility.
Keywords: Spark Ignition Engine, Fuel Consumption, Emission Factors, Simplified Combustion, Biofuel